The Phenomenon of Teachers’ Burnout: Its Implication for Job Satisfaction - De la Cruz, Joanna Mae; Macalisang, Denmark (Journal of Interdisciplinary Perspectives, 2024)
Teachers play an indispensable role in the lives of children; however, in recent years, the demands of teaching have increased significantly. This study aims to determine the feelings of burnout among secondary public-school teachers in the District of Aloran, Division of Misamis Occidental. It examines the elements contributing to teacher burnout, its impact on job satisfaction, and the coping mechanisms teachers use to mitigate it. Informant teachers, who participated in one-on-one interviews, were employed during the 2023–2024 academic year and were identified as experiencing burnout based on the results of the Maslach Burnout Inventory. A transcendental phenomenological approach and a qualitative study design were employed. The findings reveal that concerns about academics, administration, and workload demands significantly contribute to teacher burnout, affecting their well-being and hindering their professional growth. To manage burnout, teachers utilize coping strategies such as seeking social support and engaging in self-care practices. The study proposes program interventions, including upgrading and continuing current programs that support and enhance teacher well-being, along with offering competitive compensation and benefits. These findings suggest that a holistic approach addressing equity and inclusion, enhancing teacher professional development, and promoting cooperation among stakeholders will transform the school system, providing high-quality, relevant, and inclusive education.